Power Quality Improvement using Dynamic Voltage Restorer with Real Twisting Sliding Mode Control - Shah, M. S.; Mahmood, T.; Ullah, M. F.; Manan, M. Q.; Rehman, A. U. (Engineering, Technology & Applied Science Research, 2022)
Higher Power Quality (PQ) is a common demand of sensitive industrial customers. PQ issues are gaining attention from both end-users and electrical utility companies since they are generating significant economic losses to sensitive industrial loads. Voltage sags/swells are the most significant and usually occurring PQ issues in a secondary distribution system. Dynamic Voltage Restorer (DVR), is a fast, flexible, effective, and dynamic Custom Power Device (CPD), that can be used to eliminate voltage sags and swells. Its performance is mostly determined by the control strategy established for switching Voltage Source Converters (VSCs). This research work develops a fused control method for VSC of DVR based on the Real-Twisting Algorithm (RTA) and Sliding Mode Control (SMC) that successfully eliminates the impacts of voltage sags/swells. RTA along with the conventional SMC reduce the effect of chattering, which is a disadvantage of SMC while retaining its additional qualities like robustness, quicker response time, and insensitivity to load variations. To evaluate the performance of the proposed control approach, the MATLAB/Simulink SimPower System toolbox was employed. According to the simulation findings, the Real Twisting Sliding Mode Controller (RTSMC) for DVR can detect and mitigate voltage sags/swells within 2.5ms which is much lower than the allowable limit of 20ms as per semiconductor industrial equipment voltage sag immunity standard (SEMI F-47 standard) for sensitive loads. Total Harmonics Distortion (THD) is determined to be less than 5% in all simulated instances. A comparative study is also performed between the conventional SMC and the suggested RTSMC, revealing that the proposed method outperforms the classical SMC.